2018
DOI: 10.3892/ijmm.2018.3801
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin promotes osteogenic differentiation of human dental pulp stem cells

Abstract: Human dental pulp stem cells (hDPSCs) possess self-renewal and osteogenic differentiation properties, and have been used for orofacial bone regeneration and periodontal treatment. Aspirin has been demonstrated to enhance the regeneration of bone marrow mesenchymal stem cells (MSCs); however, the impact of aspirin on the osteogenic differentiation of hDPSCs remains unknown. In the present study, hDPSCs were characterized by flow cytometry, while their clonogenic potential and multipotency were assessed using al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…The IHC staining of CD146 and Runx2 showed that the AsMon treatment could recruit more mesenchymal stem cells and the releasing of aspirin promoted the osteoblast differentiation (Figure S9, Supporting Information). After 4 weeks, the AsMon‐treated group represented to have the best osteogenic effect with complete cortex formation and increased bone density (Figure h,i and Figure S10 (Supporting Information)), which might be attributed to the anti‐inflammatory ability and osteogenesis potential of aspirin released after the bactericidal phase . Above all, these results further proved that AsMon exhibited a great advantage in the treatment of osteomyelitis.…”
Section: Resultsmentioning
confidence: 60%
“…The IHC staining of CD146 and Runx2 showed that the AsMon treatment could recruit more mesenchymal stem cells and the releasing of aspirin promoted the osteoblast differentiation (Figure S9, Supporting Information). After 4 weeks, the AsMon‐treated group represented to have the best osteogenic effect with complete cortex formation and increased bone density (Figure h,i and Figure S10 (Supporting Information)), which might be attributed to the anti‐inflammatory ability and osteogenesis potential of aspirin released after the bactericidal phase . Above all, these results further proved that AsMon exhibited a great advantage in the treatment of osteomyelitis.…”
Section: Resultsmentioning
confidence: 60%
“…The osteo/odontogenic differentiation potential of DPSCs is the most widely reported. Both in vitro and in vivo experiments showed that DPSCs are able to differentiate into osteo/odontoblasts and form bone and dentin tissues [ 65 67 ]. When DPSCs are cultured in osteo/odontogenic induction medium, a group of proteins related to mineralization tissues are upregulated.…”
Section: Dpscsmentioning
confidence: 99%
“…Hao, Shi, Zhou, Wang, and Nie () showed that aspirin could enhance cardiomyocyte differentiation of bone marrow mesenchymal stem cells. Yuan et al () demonstrated that aspirin could promote osteogenic differentiation of human dental pulp stem cells. Interestingly, S. Chen et al () have reported that IL‐6 inhibited tenogenic differentiation via the JAK/STAT‐3 signaling pathway in TSCs, and our previous study has shown that aspirin significantly inhibited expression of IL‐6 (Wang, He, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hao, Shi, Zhou, Wang, and Nie (2018) showed that aspirin could enhance cardiomyocyte differentiation of bone marrow mesenchymal stem cells. Yuan et al (2018) demonstrated that aspirin could promote osteogenic differentiation of human dental pulp stem cells.…”
Section: Decades Of Research On Tendon Injuries and Regeneration Hasmentioning
confidence: 99%